Cooperation between higher education institutions and companies from a spatial perspective: An empirical analysis of Germany using Bayesian logistic multilevel models - Christian Warnecke; Daniel Weller (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
This research paper aims at highlighting factors which influence the spatial focus of interactions between higher education institutions (HEIs) and the economic system in Germany. In the pursuit of this goal, our research work employs a Bayesian statistical analysis of empirical data gathered from a German-wide online survey of professors (7,500 participants) focused on the extent of knowledge diffusion with respect to their institutions of origin. The results provided by our statistical analysis indicate that some fields of research are favourable in facilitating cooperation between companies and University professors in the region, while others are more prone to cooperate supraregional. In the case of professors at Universities of Applied Sciences (UAS), the results reveal only a low influence concerning the research discipline. These findings are not surprising because of the narrow spectrum of research disciplines at UAS. Beyond these results, the time budget allocated for research poses as a major factor of influence for the cooperation activities of professors at UAS. These findings have been expected since UAS professors have less allocated time for research leading to a more regional focus of cooperation with companies. Surprisingly across all models, only a very few categories in total are credible for the "Application relevance of research" and the "Cooperation intensity". – – In dieser Forschungsarbeit werden Faktoren aufgezeigt, die Einflüsse auf den räumlichen Schwerpunkt von Kooperationen zwischen Unternehmen und Hochschulen in Deutschland ausüben. Die Analysen stützen sich dabei auf bayesianische Modellierungen unter Verwendung empirischer Daten einer deutschweiten Professorenbefragung (N = 7.500) aus dem Jahr 2013, die insbesondere auf Nutzungshäufigkeit und Reichweite unterschiedlicher Wissenstransferkanäle abzielte. Die Modelle zeigen, dass im Fall der Universitätsprofessoren die Fachzugehörigkeit einen deutlichen Effekt auf den Kooperationsschwerpunkt hat. Hinsichtlich der Professoren an Fachhochschulen hat die jeweilige Disziplinarität nur einen geringen Einfluss. Aufgrund des begrenzten Fächerspektrums der Fachhochschulen überraschen diese Ergebnisse nicht. Darüber hinaus hat sich für die Gruppe der Professoren an Fachhochschulen das Zeitbudget für Forschung als wichtiger Einflussfaktor für den räumlichen Fokus von Kooperationen herausgestellt. Überraschenderweise ließen über alle Modelle hinweg nur sehr schwache Einflüsse der Konstrukte "Anwendungsrelevanz der Forschung" und "Kooperationsintensität" statistisch nachweisen.
Keywords: I23; I25; O32; O31; O33; R12; 330; university-industry links; knowledge transfer; collaborative research; Bayesian multilevel analysis; spatial analysis; German-wide survey